Analysis of Volatility and Stock Risk in Energy Sector Companies Using The ARCH/GARCH Method - Sulisti, Nanda; Nusantara, Agung (Economics and Business International Conference Proceeding, 2024)
Events of geopolitical conflict and the stipulation of Presidential Decree No. 112 of 2022 change the prices of energy commodities, such as oil prices which are increasing and coal prices are falling. This situation influences share price movements and investor transactions. This research is a time series analysis research by looking at event studies . The aim of this research is to determine the volatility and risk patterns of shares of energy sector companies, namely ADRO, PGAS and POWR. The method used in this research is the ARCH-GARCH model and value at risk calculations . Based on the results of this research, it can be concluded that the three companies contain the ARCH( 1) and GARCH(1,1) phenomena. The volatility patterns of the ADRO and PGAS variables are sensitive to events that occur so they are highly volatile. Based on the analysis of volatility patterns and value at risk calculations , it can be concluded that POWR has the lowest volatility and risk patterns compared to ADRO and PGAS.